5t+11=7t-13

Simple and best practice solution for 5t+11=7t-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5t+11=7t-13 equation:


Simplifying
5t + 11 = 7t + -13

Reorder the terms:
11 + 5t = 7t + -13

Reorder the terms:
11 + 5t = -13 + 7t

Solving
11 + 5t = -13 + 7t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-7t' to each side of the equation.
11 + 5t + -7t = -13 + 7t + -7t

Combine like terms: 5t + -7t = -2t
11 + -2t = -13 + 7t + -7t

Combine like terms: 7t + -7t = 0
11 + -2t = -13 + 0
11 + -2t = -13

Add '-11' to each side of the equation.
11 + -11 + -2t = -13 + -11

Combine like terms: 11 + -11 = 0
0 + -2t = -13 + -11
-2t = -13 + -11

Combine like terms: -13 + -11 = -24
-2t = -24

Divide each side by '-2'.
t = 12

Simplifying
t = 12

See similar equations:

| 2x-16=3x-12 | | -2y-6=-10 | | F-(-40)=-12 | | 6a/6=0.96/6 | | 5(m-3)+2m=2 | | x+9=1.5 | | (7+2i)+(1-4i)=0 | | x^2=-2x-3x | | .37+1.1x=2.65x-1.18 | | 12=3(p+2) | | 3n-6=-15 | | -.8x=10 | | 5x^2+3x-21=6-3x | | 40-4x=1x | | 6*(-2)=7-4y | | 1.4+x=3.6 | | 12t+36=-64-8t | | 9z-14-3z+2=0 | | -10+9y=12-2y | | 24+56x+49x^2=0 | | 25a+15=14a-29 | | z+2.5z-2.1=3(z+2.8) | | x/7=9 | | 25a+3=14a-29 | | -(5x-6)+13x=46 | | h+2h+4h-2h=10 | | 2y+(7*5)=4 | | 16-4X(-5)+8= | | 2z+2(-3z-2)=40 | | 33=-9w | | 6r-4r=-12 | | x+8+11x+4= |

Equations solver categories